(untitled) (Nexo Revista Científica, 2021)
In the context of growing competition between rail transport and other transport types, there is a need to improve the transportation process. In modern conditions, railway transport is the main link in the logistics chain of moving goods from the shipper to the receiver. The efficiency of the railway transport complex can be improved by using logistics principles in the organization of local work on the network sections. In this study, we suggest ways to solve the problem of improving the quality of service for freight owners and the efficiency of organizing local work, which is relevant for railways. To make decisions aimed at improving the efficiency of the organization of local work, a procedure for determining the costs of organizing and promoting local trains was developed, taking into account the costs on maintaining the railway infrastructure. Not only the operational activity of the railways, but also the quality of transport customers service, compliance with the regulatory deadlines for cargo delivery, depends on the choice of the optimal option for organizing local car traffic into trains and their promotion along the section. The option is selected by comparing the costs for each of the possible options for organizing local car traffic into trains and moving them along the section.